(untitled) - Davis, Gordon B. (Tokyo, 1974)
Management Information Systems provides comprehensive and integrative coverage of essential new technologies, information system applications, and their impact on business models and managerial decision-making in an exciting and interactive manner.
Keywords: Management information systems,Hệ thống thông tin quản lý